Working toward a Low-Carbon AAG Meeting: What the GHG Metrics Tell Us. Issue 1 (2nd January 2022) - Walenta, Jayme; Castro, Aylin
Abstract : As part of a special section on academic knowledge production in an age of climate disruption, this article engages with broad academic discussions on the intersection of conference travel and climate action. Specifically, we undertake a carbon footprint assessment of the travel emissions associated with the American Association of Geographers (AAG) annual gathering under three different scenarios: (1) the AAG's most recent in-person meeting in 2019 in Washington, DC; (2) the emissions impact of a meeting located in Chicago optimizing travel distance; and (3) a hub meeting model where four meetings occur simultaneously across the United States along with three smaller international hubs. Following this, we discuss the limitations to centering carbon footprints in a climate action agenda. Although footprints are illuminative, we suggest more imaginative pathways that meaningfully engage with ecological and social justice.